2007
DOI: 10.1111/j.1365-2141.2007.06534.x
|View full text |Cite
|
Sign up to set email alerts
|

Factor VIIa analogue (V158D/E296V/M298Q‐FVIIa) normalises clot formation in whole blood from patients with severe haemophilia A

Abstract: Summary This study evaluated and compared the haemostatic potential of a recombinant factor VIIa (rFVIIa) analogue (V158D/E296V/M298Q‐FVIIa, NN1731, Novo Nordisk, Denmark) with rFVIIa (NovoSeven®, Novo Nordisk). In vitro studies were performed using freshly drawn whole blood (WB) from 14 patients with severe haemophilia A and two patients with inhibitory antibodies to FVIII, comparing NN1731 and rFVIIa against a buffer control. Fourteen healthy males served as controls. Dynamic WB coagulation profiles were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

6
4

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 36 publications
7
56
0
Order By: Relevance
“…Furthermore, in investigations of the haemostatic potential of rFVIIa, it seems crucial to use human whole blood containing viable platelets. In animal models employing other species like rabbits, rats or swine, rFVIIa has a distinctly different pharmacodynamic profile [23]. Dosage of rFVIIa corresponding to an in vivo administration of 200 μg/kg was chosen in the present laboratory study to ensure an adequate and detectable effect.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in investigations of the haemostatic potential of rFVIIa, it seems crucial to use human whole blood containing viable platelets. In animal models employing other species like rabbits, rats or swine, rFVIIa has a distinctly different pharmacodynamic profile [23]. Dosage of rFVIIa corresponding to an in vivo administration of 200 μg/kg was chosen in the present laboratory study to ensure an adequate and detectable effect.…”
Section: Discussionmentioning
confidence: 99%
“…19,20,25 An early study that used TEG to individualize therapy in 3 inhibitor patients led to identification of the lack of effect of rFVIIa in 1 patient (which the patient's mother had in fact suspected), while reducing the overall use of bypassing agents in 2 other patients led to more costeffective care without compromising efficacy. 20 This study also demonstrated the utility of TEG in assessing the effects of bypassing agents used in a combination for severe bleeds.…”
Section: Prediction Of Response To Bypassing Agentsmentioning
confidence: 99%
“…Hyperfibrinolysis was generated adopting a setup previously used by our group in evaluation of clot stability. 22,23 Recombinant human single-chain tissuetype plasminogen activator (American Diagnostica Inc., Stamford, CT, final concentration 2 nM) was added to the WB sample immediately before processing the coagulation analysis. Heparin-induced Coagulopathy.…”
Section: In Vitro Development Of Investigated Coagulopathiesmentioning
confidence: 99%